On free vector balleans - Protasov, I.; Protasova, K. (Algebra and Discrete Mathematics, 2019)
A vector balleans is a vector space over R endowed with a coarse structure in such a way that the vector operations are coarse mappings. We prove that, for every ballean (X, E), there exists the unique free vector ballean V(X, E) and describe the coarse structure of V(X, E). It is shown that normality of V(X, E) is equivalent to metrizability of (X, E).